Ms Student: IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE PADA MATERI MENULIS SURAT RESMI KELAS VII DI SMP NEGERI 6 PERCUT SEI TUAN - Sipayung, Dear; Rosmaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low ability of students in writing formal letters, particularly in terms of letter structure, writing format, and the use of appropriate language conventions. In addition, students’ participation in writing activities was still relatively low because the learning model applied in the classroom was not sufficiently varied. This study aimed to describe the implementation of the Round Table cooperative learning model and to identify the results of its application in teaching formal letter writing to seventh-grade students at SMP Negeri 6 Percut Sei Tuan. This research employed a descriptive qualitative approach. The data were collected through observation, interviews, and documentation. The data sources consisted of the Indonesian language teacher and students’ formal letter writing assignments. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The findings showed that the implementation of the Round Table cooperative learning model was carried out through several systematic stages, including the formation of heterogeneous groups, collaborative writing activities, exchange of group work, feedback sessions, and evaluation of discussion results. The application of this model was able to increase students’ active participation, cooperation, and involvement during the learning process. Furthermore, the results of students’ writing in the second worksheet showed improvement compared to the first worksheet, especially in terms of the completeness of formal letter structure, appropriateness of writing format, use of formal language, and application of Indonesian spelling conventions. Therefore, the Round Table cooperative learning model can be effectively implemented to improve students’ formal letter writing skills.